Reflective effects of micro-teaching and field experiences on pre-service teachers in Nigeria. - Rosita O. Igwe,; Ngozi E. Uzoka,; Saheed Ahmad Rufai, (Penerbit Universiti Kebangsaan Malaysia, 2013)
In recent times, there have been much hues and cries over the continuous poor standard of education in Nigeria. This has been blamed predominantly on the teachers, their teaching methods and techniques, attitude to work, competence and general behavior. This unpleasant development somewhat put to question the efficacy of teacher education content particularly micro-teaching which serves as the meeting point of both theory and practice in the pre-service training of teachers. The purpose of this study is to investigate the modes of improving the pre-service teacher competence and productivity based on the constructive reflection of student teaching, with a focus on micro-teaching which is adjudged as an avenue for acquiring pre-service pedagogical knowledge and field experiences. The study seeks to highlight the efficacy of micro-teaching in facilitating effective teacher preparation. It employs a combination of quantitative and qualitative research methods. In its quantitative dimension, the study features a descriptive survey design with research questionnaire administered on 500 respondents randomly sampled across five institutions. In its qualitative dimension, the study employs inductive and deductive research methods and analysis where data were collected and analysed based on existing framework and emerging themes on reflective effect of micro-teaching and field experiences, as decided in advance by the researchers. The study revealed that micro-teaching content, resources and material need to be reviewed for optimum result. Multi channel-viewing and other forms of Information Communication Technology (lCT) gadgets need to be introduced as a matter of urgency.